Perlindungan Hukum Bagi Konsumen Terhadap Produk Makanan Olahan Non Muslim - Anggriana, Anggita; Nurhidayati, Syssy (Palita: Journal of Social Religion Research, 2023)
Nowadays, the culinary business has become a promising business for the future. Many people are interested in visiting various areas because one of them is the culinary delights of that area. The city of Singkawag is a city that is famous for its culinary delights. Still, those involved in the business are non-Muslim communities, so the halalness of the products being marketed is a matter of doubt for the Muslim community itself. This research is normative legal research. The approach used in this research is a statutory approach and a conceptual approach. This research aims to ensure that Muslim consumers in Singakwang City are more assured of the halal quality of their food. It also emphasizes the importance of halal certification for the marketed processed food. The government needs to monitor the halal labels used by each business entity because many of the halal labels used do not have halal certification. The government must review the halal certification process, especially the time and costs so that small and medium businesses in Singkawang City can also carry out halal certification for their products. The government's role in controlling the halal labels used by each business entity must continue to be fulfilled, particularly by carefully checking whether the brands installed are halal-certified.Â